Human evolution as a series of positive feedbacks - Kozłowski, Jan (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2018)
Perhaps in last few centuries not any big theory has resulted in so much opposition as Darwinian theory of evolution. Within this theory, claim that Homo sapiens evolved from animal ancestors, namely apes, is undoubtedly the most controversial issue. Long tradition of teaching by Church that a pair of first people was created in short time in Eden Garden is in contradiction to discoveries of biology, including paleontology. If God exists, which is not the research subject of science, he created human beings by a long process of biological Darwinian evolution followed by shorter process of non-Darwinian cultural evolution. Biologist must treat Homo sapiens as just one more species with long phylogeny, albeit special species characterized by brains of enormous size, with well-developed neocortex and very special mental traits being the consequence of such brain. The paper considers selection forces toward increase of this extremely expensive organ, draining at least 20% of energy. The main idea is that a series of positive feedbacks were responsible for the development of brain, correlated increase of intelligence and development of culture. Although no great breakthrough is required for such mode of evolution, energetic constrain limiting brain size was present through large part of our evolution, which was first broken by using primitive tools for cutting meat and grinding down seeds, then by thermal processing of food. The new constrain on skull size, and correlated brain size, that is the danger of death of both mother and child during childbirth, has been partly relieved by shifting large part of brain development to postnatal period. Resulting very long childhood was a prerequisite to cultural development of our species.